2005
DOI: 10.1002/cbf.1289
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of hepatotoxic and nephrotoxic effects of aroclors 1221 and 1254 in female rats

Abstract: Polychlorinated biphenyls (PCBs) are persistent environmental pollutants. This study compared effects of two PCB mixtures, Aroclors 1221 (A1221) and 1254 (A1254) on serum levels of aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), urea, creatinine and uric acid in female rats. Histopathological changes in the liver and kidney were also examined. A group of adult Wistar rats served as controls. Groups II and III were subcutaneously injected with A1221 and A1254 at 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…The increases in ALT and AST activity in response to the administration of methomyl agree with those observed by Guilhermino et al (1998) and Ashour (1999) for parathion administration. The elevation in serum transaminase activitywas also noticed by Regon et al (1994) for carbaryl, which suggests liver injury (Guilhermino et al, 1998;Kutlu et al, 2005), and may be attributable to some cell damage leading to leakage of enzymes into the blood (Dewan et al, 2004). Funakoshi et al (1995) reported that parathion and cadmium increased serum enzymes (ALT, AST and ALP).…”
Section: Discussionsupporting
confidence: 52%
“…The increases in ALT and AST activity in response to the administration of methomyl agree with those observed by Guilhermino et al (1998) and Ashour (1999) for parathion administration. The elevation in serum transaminase activitywas also noticed by Regon et al (1994) for carbaryl, which suggests liver injury (Guilhermino et al, 1998;Kutlu et al, 2005), and may be attributable to some cell damage leading to leakage of enzymes into the blood (Dewan et al, 2004). Funakoshi et al (1995) reported that parathion and cadmium increased serum enzymes (ALT, AST and ALP).…”
Section: Discussionsupporting
confidence: 52%
“…In relation to the histopathological study, tubules and glomeruli degeneration have been observed in female rats after exposure to persistent environmental pollutants such as PCBs (Kutlu et al, 2007). Moreover, after administration of streptozotocin and gentamicin (renal toxicants) necrosis and vacuolization in the proximal tubular epithelial were observed (Muruganandan et al, 2002;Pedraza-Chaverrí et al, 2004).…”
Section: Discussionmentioning
confidence: 96%
“…In this study, we focused on the effect of CRF on obesity development because of consumption of an HFD in C57BL/6 mice. The LC‐MS/MS results showed that the CRF used in this study contains 13.35% capsicoside G. The doses of CRF (10 or 100 mg/kg) used in our study did not induce hepatotoxicity or nephrotoxicity in mice, as plasma levels of AST, ALT, BUN, and creatinine were unaffected by CRF supplementation (Kutlu et al ., ). The weekly food intake of mice fed an HFD was lower than that of mice fed a ND, and there were significant differences among the HFD fed groups.…”
Section: Discussionmentioning
confidence: 99%